2019
DOI: 10.1111/nph.15671
|View full text |Cite
|
Sign up to set email alerts
|

Scent chemistry is key in the evolutionary transition between insect and mammal pollination in African pineapple lilies

Abstract: Summary Volatile emissions may play a key role in structuring pollination systems of plants with morphologically unspecialised flowers. Here we test for pollination by small mammals in Eucomis regia and investigate whether its floral scent differs markedly from fly‐ and wasp‐pollinated congeners and attracts mammals. We measured floral traits of E. regia and made comparisons with insect‐pollinated congeners. We observed floral visitors and examined fur and faeces of live‐trapped mammals for pollen. We determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 69 publications
(130 reference statements)
2
28
0
Order By: Relevance
“…When the pollinator shift is observed within a plant species, some plants adapt their floral traits to pollinators in each region (Boberg et al, 2014;Johnson & Steiner, 1997;Nagano et al, 2014;Wester et al, 2019). In M. macrocarpa, flowers were smaller in Thailand than in other regions (Table 5).…”
Section: Comparison Of Pollination System Of M Macrocarpa Among Dimentioning
confidence: 99%
See 2 more Smart Citations
“…When the pollinator shift is observed within a plant species, some plants adapt their floral traits to pollinators in each region (Boberg et al, 2014;Johnson & Steiner, 1997;Nagano et al, 2014;Wester et al, 2019). In M. macrocarpa, flowers were smaller in Thailand than in other regions (Table 5).…”
Section: Comparison Of Pollination System Of M Macrocarpa Among Dimentioning
confidence: 99%
“…However, sugar composition is not different, and M. macrocarpa secrets sucrose-dominant nectar in all regions (Table 5). In addition to flower shape and nectar characteristics, floral color and odor are also important for attracting mammalian pollinators (Faegri & van der Pijl, 1979;Johnson et al, 2011;Knudsen & Tollsten, 1995;Wester et al, 2019). The flowers of M. macrocarpa have pale green and purple petals in all regions.…”
Section: Comparison Of Pollination System Of M Macrocarpa Among Dimentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our discovery points out to future exciting research: (1) assess the efficiency of opossums as pollinators based on experiments of pollen load and fruit set; (2) set up exclusion experiments to quantitatively assess the relative importance of mammals, hummingbirds, and hymenopterans as pollinators; (3) uncover another important key trait related to non‐flying mammal pollination, which is the analyses of the chemical compounds of the floral scent and nectar. Since most Balanophoraceae species so far studied are regarded as pollinated by invertebrates and chemical traits of flower volatiles play a fundamental role in pollinator shifts from insects to mammals (see Wester et al ), S. fungiforme may be an important model to help broaden our understanding on the evolution of pollination systems in flowering plants. We also expect that future observations may indicate a greater importance of non‐flying mammals as pollinators of other Balanophoraceae species.…”
mentioning
confidence: 99%
“…In another intriguing study on the evolution of mammal pollination – an uncommon event in plant evolution – Wester et al . () demonstrated that it was primarily changes in floral scent, and not floral morphological changes, that have altered to attract mammalian pollinators.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yeamentioning
confidence: 99%